THE IMPLEMENTATION OF THERAPEUTIC COMMUNICATION OF NURSES TO THE PARENTS OF PEDIATRIC PATIENTS IN PRE-OPERATIVE STAGE - Fanny Adistie; Henny Suzana Mediani; Ikeu Nurhidayah; Sri Hendrawati (Belitung Raya Foundation, Indonesia, 2018)
Background: The pre-operative care aims at preparing the patient and family to face the surgery. In providing nursing care to the pediatric patients, it is better and is recommended that the nurse demonstrate a therapeutic communication. Objective: This study aims to identify the implementation of the therapeutic communication by nurses to the parents of the pediatric patients who will undergo surgery in the pediatric surgical ward based on the perspective and expectation of the parents. Methods: The study used a mixed method, with the strategy of sequential explanatory. The quantitative study involved 101 respondents. The implementation of therapeutic communication is measured by using the questionnaire of therapeutic communication implementation. The qualitative study was conducted to six participants as samples, with analysis interactive model technique. Results: The result of quantitative study found that 53.5% identified poor therapeutic communication being implemented by nurses to the parents of the patients. The result of the qualitative study foundthat parents expect comprehensive therapeutic communication from nurses, both in terms of language or behavior in any delivery of information or actions to be performed. Conclusion: The result of this study is expected to be an input for the health care institutions, especially to make it as a reference for consideration in making the standard operating procedures on the implementation of therapeutic communication to improve the nurses’ quality of care.